LO48: Pediatric cannabinoid hyperemesis syndrome in the emergency department: a 5-year retrospective review. (May 2020) - Foster, D.; Aarsen, K. Van; Yan, J.; Teefy, J.; Lynch, T.
Abstract : Introduction: Cannabinoid Hyperemesis Syndrome (CHS) in pediatric patients is poorly characterized. Literature is scarce, making identification and treatment challenging. This study's objective was to describe demographics and visit data of pediatric patients presenting to the emergency department (ED) with suspected CHS, in order to improve understanding of the disorder. Methods: A retrospective chart review was conducted of pediatric patients (12-17 years) with suspected CHS presenting to one of two tertiary-care EDs; one pediatric and one pediatric/adult (combined annual pediatric census 40, 550) between April 2014-March 2019. Charts were selected based on discharge diagnosis of abdominal pain or nausea/vomiting with positive cannabis urine screen, or discharge diagnosis of cannabis use, using ICD-10 codes. Patients with confirmed or likely diagnosis of CHS were identified and data including demographics, clinical history, and ED investigations/treatments were recorded by a trained research assistant. Results: 242 patients met criteria for review. 39 were identified as having a confirmed or likely diagnosis of CHS (mean age 16.2, SD 0.85 years with 64% female). 87% were triaged as either CTAS-2 or CTAS-3. 80% of patients had cannabis use frequency/duration documented. Of these, 89% reported at least daily use, the mean consumption was 1.30g/day (SD 1.13g/day), and all reported ≥6 months of heavy use. 69% of patients had at least one psychiatric comorbidity. When presenting to the ED, all had vomiting, 81% had nausea, 81% had abdominal pain, and 30% reported weight loss. Investigations done included venous blood gas (30%), pregnancy test in females (84%), liver enzymes (57%), pelvic or abdominal ultrasound (19%), abdominal X-ray (19%), and CT head (5%). 89% of patients received treatment in the ED with 81% receiving anti-emetics, 68% receiving intravenous (IV) fluids, and 22% receiving analgesics. Normal saline was the most used IV fluid (80%) and ondansetron was the most used anti-emetic (90%). Cannabis was suspected to account for symptoms in 74%, with 31% of these given the formal diagnosis of CHS. 62% of patients had another visit to the ED within 30 days (prior to or post sentinel visit), 59% of these for similar symptoms. Conclusion: This study of pediatric CHS reveals unique findings including a preponderance of female patients, a majority that consume cannabis daily, and weight loss reported in nearly one third. Many received extensive workups and most had multiple clustered visits to the ED.